POLA KOMUNIKASI TATA KELOLA RESTRUKTURISASI (STUDI KASUS REORGANISASI BADAN PERENCANAAN DAN PEMBANGUNAN KOTA AMBON) - RIDO LATUHERU (BADATI, 2020)
Organizational communication patterns, in this case the Ambon City Planning and Development Agency,as we all know that the communication pattern in the organizational structure is a form of messageexchange interaction between organizational members, both verbal and non-verbal communication. Forthis reason, a form of communication poa between superiors and subordinates and subordinates andsubordinates is needed so that the office work process and task completion can run effectively andefficiently. Formulation of the problem What is the Communication Pattern of Restructuring Governancethat occurs in the Ambon City Planning and Development Agency?Research objectives 1) Knowing the suitability of the organizational restructuring of the regionalapparatus in the Ambon City Planning and Development Agency. 2) To know, and understand theCommunication Patterns of the Ambon City Planning and Development Agency. 3) Communication andCoordination Patterns that arise after the Restructuring.The research method involves: 1) The research site is carried out in the Ambon City Planning andDevelopment Agency. 2) The research approach used a descriptive qualitative approach. 3) The techniqueof collecting data uses observation, documentation, deep interview, library research techniques.The results of the study are in the form of a conclusion that there is a preventive step from the leadershipof the Ambon City Planning and Development Agency in formulating a communication pattern besides thatthe existing organizational restructuring process has put forward the concept of poor, rich-functionstructure so that it can support employee work processes.